Competency Mastery of Information Literacy and Collaboration on Prospective Teacher Students - Syah, Muhammad Fahmi Johan; Harsono, Harsono; Prayitno, Harun Joko; Fajriyah, Desi Susanti (Dinamika Pendidikan, 2019)
This study aims to describe and explore the achievement of competencies in information literacy and collaboration skills as part of 21st century competency in accounting education students at the Muhammadiyah University of Surakarta (UMS). The respondents of this study were 207 students with a mixed method approach through convergent parallel design. The results of the study showed that most students had information literacy skills but were still relatively low. This can be seen from students who had mostly used the internet, but did not use trusted sources. This condition is exacerbated by students not filtering and validating the information so that the information submitted tends to be biased, only a few used credible journals as a reference while the rest used sources whose information credibility was still doubtful. In collaboration skills, the achievement of this competency varies between students who are active in campus organizations, non-campus organizations, and do not follow any organization. Those who were active in the organization seem to be better at mastering this competency. This can be seen in the aspect of contributions in groups and accepting responsibility. Courage to accept new responsibilities was not fully owned, some were still hesitant to accept the responsibility given to him for various reasons, especially those classified as inactive organizations. In this aspect, it appears that students who were active in non-campus organizations considered a mandatory task to be disliked. Whereas in the aspect of collective responsibility, students both active and non-active in organizations had the same competencies where they wanted and were able to work together in teams.